Pengaruh Perlakuan Termomekanik pada Paduan Titanium Ti-5Mo-9Nb - Sutowo, Cahya; Rokhmanto, Fendy; Prasetyo, Agus Budi; Utama, Dedi Pria (Universitas Pamulang, 2025)
Until now, more than 95% of the material needs for medical devices are still imported, independent mastery of technology can at least reduce dependence on imported implant materials. On the one hand, the increase in the welfare of the population in Indonesia today is directly proportional to the increase in life expectancy of the population. The above conditions will have an impact on the increase in the number of elderly people. The increase in the elderly population will potentially increase the occurrence of degenerative bone diseases suffered by the elderly. This study aims to analyze the effect of the thermomechanical process through hot rolling. The added Mo and Nb elements function as beta phase stabilizers which will certainly affect the microstructure and mechanical properties of titanium alloys. The thermomechanical heat treatment process is an advanced process where the homogenized ingot is then hot rolled at a temperature of 1100 °C in 3 rolling stages until it reaches a 50% reduction. Then characterized by observing the microstructure and mechanical properties. The thermomechanical process involves plastic deformation at high temperatures that affect changes in microstructure and mechanical properties. Plastic deformation combined with recrystallization results in smaller grain sizes, which improves mechanical properties with a relatively uniform increase of 429–450 VHN. Therefore, this thermomechanical processed Ti-5Mo-9Nb-based alloy has the potential for improved medical implant material applications. Abstrak: Sampai saat ini kebutuhan material untuk alat kesehatan lebih dari 95% masih impor, penguasaan teknologi secara mandiri setidaknya dapat mengurangi ketergantungan impor material implan. Di satu sisi, peningkatan kesejahteraan penduduk di Indonesia dewasa ini berbanding lurus dengan meningkatnya usia harapan hidup penduduk. Kondisi tersebut di atas akan berdampak terhadap peningkatan jumlah penduduk usia lanjut. Meningkatnya penduduk usia lanjut akan berpotensi pada terjadinya penyakit tulang degeneratif yang diderita oleh para lanjut usia akan semakin meningkat. Penelitian ini bertujuan untuk menganalisis pengaruh proses termomekanik melalui pengerolan panas. Unsur Mo dan Nb yang ditambahkan berfungsi sebagai penstabil fasa beta yang tentunya akan memengaruhi struktur mikro dan sifat mekanis paduan titanium. Proses perlakuan panas termomekanik merupakan proses lanjutan di mana ingot yang telah dihomogenisasi kemudian dilakukan pengerolan panas pada temperatur 1100 °C sebanyak 3 tahapan pengerolan sampai mencapai reduksi 50%. Kemudian dikarakterisasi melalui pengamatan struktur mikro dan sifat mekanik. Proses termomekanik melibatkan deformasi plastis pada suhu tinggi yang memengaruhi perubahan mikrostruktur dan sifat mekanis. Deformasi plastis yang dikombinasikan dengan rekristalisasi menyebabkan ukuran butir menjadi lebih kecil, yang meningkatkan sifat mekanis dengan peningkatan yang relatif seragam 429–450 VHN. Sehingga paduan berbasis Ti-5Mo-9Nb melalui proses termomekanik ini berpotensi untuk aplikasi material implan medis yang lebih baik.